A Critical Analysis of the Adolescent Pregnancy Prevention Bill - Dionisio-Sese, Floribert; Barrot, Rubenito; Juinio-Meñez, Marie Climacosa; Agoncillo, Michael (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2023)
Teenage pregnancy remains a major public health and social development concern in the Philippines, with adolescent birth rates among the highest in Southeast Asia. In response, policymakers introduced the Adolescent Pregnancy Prevention Bill, which aims to institutionalize Comprehensive Sexuality Education (CSE). However, the bill has sparked polarized responses from various stakeholders, revealing tensions between moral conservatism and rights-based public health advocacy. This study investigates how the bill is discursively framed in media and policy narratives and how such framings influence public perception and policy legitimacy. Adopting a qualitative design, it employs Critical Discourse Analysis (CDA) to examine 50 news articles and 200 social media posts, complemented by six semi-structured interviews with policymakers, youth advocates, and religious leaders. Findings reveal a clash between moral protectionist and public health frames, each claiming to safeguard youth but operating on distinct emotional and ideological logics. The legitimacy of the bill is further undermined by low institutional trust, especially in local governments and education agencies. Youth are often excluded from formal policy discourse but emerge as both vulnerable and active participants in digital spaces where misinformation also thrives. The study argues that successful sexuality education reform requires reframing efforts that align moral and health narratives, rebuild institutional credibility, and meaningfully integrate youth voices. Future research should explore hybrid communication strategies and youth-led policy design as tools for bridging ideological divides.